Improving the cycling and air-storage stability of LiNi0.8Co0.1Mn0.1O2 through integrated surface/interface/doping engineering. Issue 10 (26th February 2020) - Zhai, Yanwu; Yang, Wenyun; Ning, De; Yang, Jinbo; Sun, Limei; Schuck, Götz; Schumacher, Gerhard; Liu, Xiangfeng
Abstract : Excellent cycling and air-storage stability of LiNi0.8 Co0.1 Mn0.1 O2 are obtained through an integrated strategy with a Li2 ZrO3 protective layer, Zr 4+ doping and the rock-salt interface phase engineering from Li2 ZrO3 coating. Abstract : The poor cycling performance and storage instability of Ni-rich layered oxide cathode materials seriously restrict their practical application. Herein, we report to improve the cycling and air-storage stability of LiNi0.8 Co0.1 Mn0.1 O2 through integrated surface/interface/doping engineering. The capacity retention after 500 cycles at 5C is largely enhanced from 69.6 to 80.6%. After 70 days of storage in air, the initial discharge capacity at 5C is 143.1 mA h g −1 and the capacity retention after 500 cycles is 88.5%. The cycling and air-storage stability can be attributed to the integration of the Li2 ZrO3 protective layer, Zr 4+ doping and the rock-salt interface phase from Li2 ZrO3 coating. The Li + -conductive Li2 ZrO3 layer suppresses the side reaction as well as enhances the Li-ion diffusion at the interface. In the meantime, Zr 4+ doping enlarges the lithium slab thickness and decreases Li/Ni disorder, which further enhances Li-ion diffusion in the bulk. Zr 4+ doping makes TM–O bonds more stable and alleviates the lattice changes during charge–discharge cycles owing to the strong Zr–O bond. Moreover, the formed rock-salt phase on the interface further enhances the stability of the layered structure. More importantly, the Li2 ZrO3 coating suppresses the formation of an electrochemically insulating substance on the cathode surface, which dramatically improves the long term air-storage stability.